VALUABLE MORAL MESSAGES IN THE CLASSICAL ARABIC POETRY: SEMIOTIC STUDY OF THE IMAM ALI'S POEMS - Arifianto, Muhammad Lukman (Arabi : Journal of Arabic Studies, 2020)
This paper discusses the moral messages implied in the Imam Ali's poems. As stated by some experts, poetry is a set of signs that need to be sought for its meaning and significance. This set of signs is mostly difficult to be realized directly by ordinary people. In consequence, Imam Ali's poems need to be explored by semiotic analysis so that the meanings implied in these poems can be elaborated in detail, and hopefully, it can be well understood by the public. The method used is descriptive-analytical framework that emphasizes systematic interpretation from of the individual point of view or population being studied to generate new concepts. Based on the result, it is found that Imam Ali's poems imply many valuable and important moral messages that were in line with Islamic teachings and they are very important to be known, studied, and used as the guidelines in everyday life. The moral messages implied in these poems they are about the primacy of seeking knowledge and science, the primacy of reasoning, the primacy of silence, keeping away from greedy, and patient with all kinds of insult.